Zeolite modification for optimizing Fenton reaction in methylene blue dye degradation - Carvalho, Ana P. (2025)
Textile dyes often prove resistant to conventional wastewater treatment processes because of their complex molecular structures. Advanced oxidation methods, such as the Fenton reaction, have thus been recognized as a promising approach for environmental remediation by decomposing these pollutants. This work aimed to study the efficacy of modified zeolites as catalysts in the Fenton reaction for dye degradation, with a particular emphasis on techniques for modifying zeolites and incorporating iron. The zeolite ZSM-5 was selected as the parent structure and underwent desilication and acid treatment procedures. Iron was introduced into the zeolite structure via two distinct methods: ion exchange and mechanochemistry. The modified zeolites with incorporated iron were evaluated in terms of their crystallinity, textural properties, and iron content before being used to degrade methylene blue solutions through the Fenton reaction. The reaction was monitored using UV-Vis spectroscopy, while the experimental outcomes were analyzed using pseudo-first-order and pseudo-second-order kinetic models. The research findings indicate that different treatment methods led to varying impacts on the zeolite properties, which in turn influenced the kinetic results. Moreover, it was observed that an enhancement in the degradation process can be achieved through the harmonious balance between a high iron content, increased mesoporosity (to facilitate diffusion), and adequate crystallinity (essential for maintaining structural integrity).